2000
DOI: 10.1126/science.290.5489.150
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Protease Domain of Memapsin 2 (β-Secretase) Complexed with Inhibitor

Abstract: Memapsin 2 (beta-secretase) is a membrane-associated aspartic protease involved in the production of beta-amyloid peptide in Alzheimer's disease and is a major target for drug design. We determined the crystal structure of the protease domain of human memapsin 2 complexed to an eight-residue inhibitor at 1.9 angstrom resolution. The active site of memapsin 2 is more open and less hydrophobic than that of other human aspartic proteases. The subsite locations from S4 to S2' are well defined. A kink of the inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
686
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 692 publications
(716 citation statements)
references
References 31 publications
24
686
2
4
Order By: Relevance
“…Up to now, studies of BACE have concentrated on its structure [4,45], trafficking [11,16,[46][47][48][49][50], and specific inhibition [10], but how its activity is regulated remains largely unclear. In this study, we demonstrated that BACE activity both in vitro and in vivo could be efficiently regulated by RTKs, and the regulation of BACE activity led to alterations of subsequent Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, studies of BACE have concentrated on its structure [4,45], trafficking [11,16,[46][47][48][49][50], and specific inhibition [10], but how its activity is regulated remains largely unclear. In this study, we demonstrated that BACE activity both in vitro and in vivo could be efficiently regulated by RTKs, and the regulation of BACE activity led to alterations of subsequent Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…for 15 days) accompanied by AChE activity restoration and cognitive improvement in the Morris Water Maze test has been observed in the STZ-icv treated mice (Sharma et al 2008). This effect has been associated with the findings that HIV protease has structural homology to beta-secretase 1 (BACE) (Hong et al 2000) and thus can modulate BACE activity, and consequently, possibly, the amount of amyloid-β formation (Nunan and Small 2000). Although a quite a number of trials has been conducted with Ginkgo biloba in demented patients, a…”
Section: Nosmentioning
confidence: 99%
“…Although many different names were originally used to describe this activity, such as memapsin, aspartyl protease 2, or BACE1 (b-site APP cleaving enzyme-1), BACE1 is now the generally accepted term for the enzyme harboring b-secretase activity. BACE1 is a membrane-bound aspartyl protease with its active site in the lumen/extracellular space and with structural similarities to the pepsin family (Hong et al 2000). Besides BACE1, a homologous protease called BACE2 was identified (Vassar 2004).…”
mentioning
confidence: 99%